Seasonal and Interannual Variability of Areal Extent of the Gulf of Mexico Hypoxia from a Coupled Physical‐Biogeochemical Model: A New Implication for Management Practice. Issue 7 (10th July 2019) - Feng, Yang; DiMarco, Steven F.; Balaguru, Karthik; Xue, Huijie
Abstract: The extent of hypoxia on the Louisiana shelf has been measured during July since 1985. The measured area was assumed to represent the seasonal maximum each year and was related to the Mississippi‐Atchafalaya riverine May NO2+3 loading and May–June total nitrogen loading, for planning management strategies. In this study, we analyze 25 years of simulations from a coupled physical‐biogeochemical model. An empirical orthogonal function analysis of the hypoxia frequency reveals that the dominant pattern is east‐west, with the seasonal maximum occurring in June, July, or August. This indicates that the July hypoxic area may or may not always be the largest of the year. A simple linear regression model was constructed to examine the explained variance of hypoxia attributable to nutrients. Results reveal that the May NO2+3 (May–June total nitrogen) loading can explain 35% ± 7% (54% ± 7%) of the maximum cumulative hypoxic area in contrast to 22% ± 9% (48% ± 12%) of the July cumulative hypoxic area. Our results suggest that the current nitrogen loading reduction suggested by the Hypoxia Task Force 2013 is not sufficient to reduce the 5‐year moving average Gulf's hypoxic zone to less than 5, 000 km 2 . A reduction of at least 66% (48%) of May NO2+3 (May–June total N) loading is needed when using July hypoxic area as the criterion, while a reduction of 77% (60%) of May NO2+3 (May–June total N) loading is needed when using maximum hypoxic area. Plain Language Summary: Shelf‐wide surveys of hypoxia have been conducted in July since 1985 over the Texas‐Louisiana shelf. The measured hypoxic area has been used as the metric for hypoxia severity. Management practices have been designed based on this metric to control the amount of nitrogen loading to the Mississippi River Basin. Our analysis of 25 years of model output reveals that the reported measured area may not always be the largest of the year. Therefore, using July hypoxic area will underestimate the reduction in nutrient loading required to achieve a 5, 000‐km 2 area required reduction in nitrogen. Key Points: Monthly hypoxia frequency is predominantly east‐west, with seasonal maximum occurring in June, July, or August Satellite sea surface salinity, Chl a, and wind can be used with empirical relations to map spatiotemporally continuous bottom dissolved oxygen fields More nitrogen reduction will be needed to reduce hypoxic area to 5, 000‐km 2 target once the maximum hypoxic area could be known